PENGARUH PENAMBAHAN SERBUK GERGAJI KAYU TERHADAP PRODUKTIFITAS WAKTU DAN KUAT TEKAN BATA - Deddy Kurniawan; Muhammad Yusuf; Helga Yermadona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Bricks are one of the most widely needed materials in construction. Wood sawdust which was previously only a waste can now be used as a mixture in the manufacture of bricks. One of the methods used in this research is mixing wood sawdust on soil material to speed up the manufacture of bricks. This study used wood sawdust as much as 0%, 2%, 4%, 6%, and 8% in the manufacture of bricks. Then test the compressive strength and water absorption of the bricks. The results of the average compressive strength test in the 0% mixture obtained the results of 59.84 Kg/cm2 in the 2% mixture, the results were 50.36 Kg/cm2 in the 4% mixture, the results were 42.56 Kg/cm2 in the 6% mixture, the results were 4.42 Kg /cm2 and in the 8% mixture, the result is 3.16 Kg/cm2. after research on water absorption, the results obtained for a mixture of 0% obtained 26% results for a 2% mixture obtained 25% results for a 4% mixture obtained 31% results for a 6% mixture obtained 45% results and for a mixture of 8% obtained 45% results. Based on the analysis, the optimal mixture for this research is the addition of 2% sawdust because the results in terms of compressive strength and water absorption are close to the SNI value.